(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Fatigue is a gradual process related with an effort to keep awake, eventually resulting in declination of human performance. It is one of the well-known risk factors for traffic accidents. The objective of this study is to understand the psychophysiological aspects of driver fatigue by using driving simulator. This study had focused on heart rate (HR) measures to determine driversâ€™ performance as this method can be measured in a less intrusive manner. Hence, in this study, 17 relevant studies were discussed, chosen from electronic databases. This study encompasses a range of subject areas, including concepts and theories of fatigue, driver fatigue, and psychophysiological indicators and countermeasures of driver fatigue. A variety of psychophysiological measures and parameters have been used in past research as indicators of fatigue. Based on this review, HR can assists researchers to determine performance according to a task demand, condition and its complexity.Â The review highlighted gaps in the literature and opportunities for future studies.